2020
DOI: 10.3390/ijerph17207594
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Link between Work Addiction Risk and Health-Related Outcomes Using Job-Demand-Control Model

Abstract: Purpose of the study: Work addiction risk is a growing public health concern with potential deleterious health-related outcomes. Perception of work (job demands and job control) may play a major role in provoking the risk of work addiction in employees. We aimed to explore the link between work addiction risk and health-related outcomes using the framework of job-demand-control model. Methods: Data were collected from 187 out of 1580 (11.8%) French workers who agreed to participate in a cross-sectional study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 68 publications
(156 reference statements)
2
21
0
1
Order By: Relevance
“…A recent study suggests that academics working at Norwegian universities experience high levels of workaholism as compared to professionals in different occupations in the Netherlands, and significantly higher levels of workaholism and work-family conflict than their technical and administrative personnel colleagues (Torp, Lysfjord, & Midje, 2018). This is consistent with Dutheil et al's (2020) study who found the prevalence of work addiction risk to be greater among highly skilled occupations with high demands-"active" and "high strain" workers-and in occupations with high levels of decision latitude like academics.…”
Section: Introductionsupporting
confidence: 67%
“…A recent study suggests that academics working at Norwegian universities experience high levels of workaholism as compared to professionals in different occupations in the Netherlands, and significantly higher levels of workaholism and work-family conflict than their technical and administrative personnel colleagues (Torp, Lysfjord, & Midje, 2018). This is consistent with Dutheil et al's (2020) study who found the prevalence of work addiction risk to be greater among highly skilled occupations with high demands-"active" and "high strain" workers-and in occupations with high levels of decision latitude like academics.…”
Section: Introductionsupporting
confidence: 67%
“…A score below 24 reflects low social support [ 22 ]. In a previous study performed by our team, the Cronbach’s alphas for job demands, job control, and social support were 0.58, 0.99, and 0.99, respectively [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…The generally admitted pathological thresholds score is 8. In a previous study performed by our team in a similar population, the Cronbach’s alphas for the components of depression and anxiety were 0.82 and 0.79, respectively [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the different working conditions, workload—as a chronic feature of the job—has received the most attention as a potential antecedent of workaholism. Different studies of the Special Issue further document the role of workload either as a potential main factor in workaholism [ 19 , 24 ] or as a factor interacting with personality traits [ 25 ].…”
mentioning
confidence: 99%
“…Finally, three different studies of the Special Issue further highlight the negative outcomes associated with workaholism by examining employee turnover [ 26 ], depression and poor sleep quality [ 24 ], and behavioral and emotional problems in children of workaholic parents [ 27 ]. On the contrary, the study by Li et al [ 28 ] found that workaholism attenuated the negative relationship between work intensification and well-being.…”
mentioning
confidence: 99%